2016
DOI: 10.1016/j.brainres.2015.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Looking into the future: Using induced pluripotent stem cells to build two and three dimensional ocular tissue for cell therapy and disease modeling

Abstract: Retinal degenerative diseases are the leading cause of irreversible vision loss in developed countries. In many cases the diseases originate in the homeostatic unit in the back of the eye that contains the retina, retinal pigment epithelium (RPE) and the choriocapillaris. RPE is a central and a critical component of this homeostatic unit, maintaining photoreceptor function and survival on the apical side and choriocapillaris health on the basal side. In diseases like age-related macular degeneration (AMD), it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 119 publications
0
42
0
Order By: Relevance
“…Culture models relevant to human pathology can supplement the limitations of in vivo models. 50,51 The current study joins two others that studied RPE-related macular dystrophies by using patient-derived iPSC and age-matched controls. Saini et al 37 One concern for using iPSCs to study these diseases is that each develops over many years and iPSCs are young in that they have reverted into an embryonic-like state.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Culture models relevant to human pathology can supplement the limitations of in vivo models. 50,51 The current study joins two others that studied RPE-related macular dystrophies by using patient-derived iPSC and age-matched controls. Saini et al 37 One concern for using iPSCs to study these diseases is that each develops over many years and iPSCs are young in that they have reverted into an embryonic-like state.…”
Section: Discussionmentioning
confidence: 89%
“…Culture models relevant to human pathology can supplement the limitations of in vivo models . The current study joins two others that studied RPE‐related macular dystrophies by using patient‐derived iPSC and age‐matched controls.…”
Section: Discussionmentioning
confidence: 91%
“…For example, Singh et al demonstrated defective photoreceptor outer segment degradation and disposal as well as reduced fluid transport in iPSC-derived RPE derived from patients with the RPE-specific protein bestrophin-1 (BEST1) mutation [80]. Disease modeling with iPSC derived from monogenic degenerative disorder will benefit greatly from this technology [9,12]. …”
Section: Use Of Ipsc-derived Rpe To Model Age-related Macular Degementioning
confidence: 99%
“…The fact that these cells can be directly generated from the patient affords investigators the opportunity to model a specific disease and provides a relevant investigational tool that is an alternative to traditional animal models [9,10,11]. Use of iPSC-derived cells for disease modeling can allow for the understanding of the pathology and cell biology of retinal diseases such as AMD, and help elucidate the morphological changes attributed to the aging process and progression of disease [12,13]. These models can also lead to the development of platforms for drug screening and safety studies.…”
Section: Introductionmentioning
confidence: 99%
“…Induced pluripotent stem cells can be manufactured from some CD34+ cells isolated from 100 to 200 mL of whole blood. Clinical protocols are being developed to use iPSC‐derived retinal pigment epithelial cells to treat age‐related macular degeneration . Mesenchymal stromal cells or MSCs are being used in a number clinical trials for both regenerative medicine and immunomodulation.…”
mentioning
confidence: 99%